Hatchability evaluation of bovine IVF embryos using OCT-based 3D image analysis - Yasumitsu MASUDA; Ryo HASEBE; Yasushi KUROMI; Mitsugu HISHINUMA; Tetsuya OHBAYASHI; Ryo NISHIMURA (The Society for Reproduction and Development, 2023)
Although embryo transfer is widely applied in cattle, many of the transferred embryos do not result in pregnancy. To determine a new parameter for bovine embryo evaluation, we investigated the relationships between in vitro hatchability and embryo morphological parameters using optical coherence tomography (OCT) that we established recently. Bovine embryos were obtained from Japanese Black cattle by in vitro fertilization (IVF). The quality of the blastocysts was examined under an inverted microscope and confirmed as Codes 1-3 according to the IETS standards for embryo evaluation. The OCT images of the embryos were captured on Day 7 after IVF, and the embryos were cultured until Day 9 to determine their hatchability. During OCT, the embryos were irradiated with near-infrared light for a few minutes to obtain three-dimensional images. In total, 22 parameters were assessed for each of the 42 embryos, of which 25 hatched (H embryos) and 17 did not (NH embryos). The thickness of the trophectoderm (TE) and TE+zona pellucida (ZP) was lesser, and the volumes of the TE, ZP, blastocoel, and whole embryo and blastocoel diameter were greater in the H embryos than in the NH embryos. PCA identified that the increase in the blastocoel-related value along with the decrease in the thickness-related value of the TE and/or ZP could be indicators for evaluating the hatchability of bovine IVF embryos. These results support the idea that OCT-captured structural data of blastocyst-stage embryos can be used as a potential model to predict the quality of bovine embryos.